Recent Insights Into the Role of Macrophages in Acute Gout - Liu, Lei; Zhu, Lingjiang; Liu, Mengdan; Zhao, Li; Yu, Yiyun; Xue, Yu; Shan, Lizhen (Frontiers in Immunology, 2022)
Gout is a common type of inflammatory arthritis characterized by the presence of monosodium urate crystals (MSU) in the joints. Macrophages are believed to be involved in gout flares. It has long been recognized that resident macrophage and monocyte derived macrophages are distinct subsets and there have been attempts to investigate their roles in acute gout, respectively. Previous studies revealed that resident macrophages initiate and drive the inflammation, while monocyte derived macrophages differentiated into M1-like macrophages in response to MSU crystals. With the advancement of technologies, subpopulations of synovial resident macrophages have been defined with the characteristics more accurately described. Resident macrophages in the synovial lining layer showed an anti-inflammatory effect in rheumatoid arthritis, but specific Trpv4 depletion of them reduced MSU crystals induced murine arthritis. CD14+ monocytes in the synovial fluid from patients with gout exhibit phenotypes of anti-inflammatory as well as pro-inflammatory characteristics. Here, we review the main aspects of macrophages in the initiation and resolution of acute gout and try to clarify the specific role of each subpopulation. Building a reliable diagram of the effect of monocytes and macrophages during MSU crystals induced arthritis will bring us closer to targeting macrophages for improving the management of gout.